Digital Communication Transformation in Sukabumi City Government - Woro Harkandi Kencana; Ilona Vicenovie Oisina Situmeang; Meisyanti Meisyanti; Khina Januar Rahmawati; Herlin Setio Nugroho; Adiella Yankie Lubis (Universitas Muhammadiyah Yogyakarta, 2023)
Central and regional governments must innovate in communication technology in the fourth industrial revolution. This study aims to identify and analyze the digital communication transformation in the government of Sukabumi City through the innovative use of communication technology. This study uses the Adaptive Structuring Theory (AST) theory, which studies the adaptation of new information technology within an organization. The methodology uses a qualitative approach with primary data collection through interviews with Diskominfo and the Sukabumi City Kelurahan. Meanwhile, the FGD was conducted with the community and sub-district staff of three sub-districts in Sukabumi City, namely Cisarua, Subang Jaya, and Cikole sub-districts. The results of this study accelerated the digital communication transformation in Sukabumi City’s electronic-based government system services (SPBE). Adaptation of technology in integrated organizations impacts government systems, civil servants, business actors, and the community. Sukabumi City’s government is transforming communication in public services, complaint applications, and population administration applications to become government and community media in communicating. Meanwhile, business actors are facilitated by the city government in implementing licensing and digital marketing communications presented through government social media, which helps increase consumer engagement.